Perancangan Film Pendek Animasi 3D berjudul ”Riko & Niko” tentang Pelanggaran Aturan Penggunaan Sepeda Listrik - Nadya, Nadya; Wicaksono, Bagus Eko Satrio (Titik Imaji, 2025)
In recent times, accidents involving the use of vehicles, particularly electric bicycles, have become increasingly common. These accidents are largely attributed to the public's lack of understanding regarding proper electric bicycle usage. The scarcity of informative content on this subject also contributes to the rising number of such incidents. This observation underscores the necessity of a medium that can provide education on electric bicycles. This study employs a qualitative research approach, collecting data through observation, literature review, and questionnaires. The findings inform the design of an educational video presented in an engaging manner and tailored to the target audience in the form of a 3D animated short film. The design process follows the animation development method proposed by Nazanin Shahbazi (2024). The resulting animated short film is further supported by a distribution strategy encompassing local and national scales through social media and online platforms, aiming to raise awareness about the dangers of operating electric bicycles improperly. This research aspires to serve as an educational resource for the public and to contribute to the advancement of the Indonesian animation industry.